2023
DOI: 10.1158/2767-9764.crc-23-0072
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Ipilimumab plus Nivolumab after Anti-PD-1/PD-L1 Therapy in Advanced Hepatocellular Carcinoma

Abstract: Combination anti-PD-(L)1/CTLA-4 blockade is approved in patients with hepatocellular carcinoma (HCC) in the first-line setting or after sorafenib, but whether this treatment has efficacy after prior anti-PD-(L)1 therapy is unknown. We performed a multicenter retrospective review of patients with advanced HCC treated with ipilimumab plus nivolumab after prior anti-PD-(L)1 therapy, excluding patients with prior anti-CTLA-4 treatment. Of the 32 patients who met our inclusion criteria, prior anti-PD-(L)1 regimens … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The efficacy of drug sequencing from ICI to ICI with regimens including Atezo/Bev has been reported previously [ 14 ], with the response rate for nivolumab plus ipilimumab reported to be 16-30% in RECIST 1.1 and the rate of immune-related adverse events required systemic corticosteroid treatment reported to be 10-12% that included the Atezo/Bev regimen [ 15 - 17 ]. Tremelimumab, which has the same CTLA-4 inhibitory effect as ipilimumab, is also expected to be effective and safe.…”
Section: Discussionmentioning
confidence: 92%
“…The efficacy of drug sequencing from ICI to ICI with regimens including Atezo/Bev has been reported previously [ 14 ], with the response rate for nivolumab plus ipilimumab reported to be 16-30% in RECIST 1.1 and the rate of immune-related adverse events required systemic corticosteroid treatment reported to be 10-12% that included the Atezo/Bev regimen [ 15 - 17 ]. Tremelimumab, which has the same CTLA-4 inhibitory effect as ipilimumab, is also expected to be effective and safe.…”
Section: Discussionmentioning
confidence: 92%
“…Median OS and PFS were 9.2 and 2.9 months, respectively. The treatment was associated with irAEs, including pneumonitis and colitis/esophagitis (13% each), followed by autoimmune hepatitis (9%), rash (9%), arthritis (3%), and myocarditis (3%) [97]. Thus, these studies demonstrated that nivolumab and ipilimumab could provide a clinical benefit in patients resistant to sorafenib and other PD-(L)1 inhibitors.…”
Section: Combination Of Pd1/pd-l1 Inhibitors With Agents Targeting Ct...mentioning
confidence: 87%
“…Thus far, there have been studies indicating that the combined use of ipilimumab and nivolumab may be efficacious and well-tolerated following prior ICI-based combination therapies. This underscores the need for prospective clinical assessments of this treatment sequence [105,106] (Table 2).…”
Section: Employment Of Cd8+ T Lymphocytes In Immunotherapymentioning
confidence: 99%